Penguasaan Teori Hukum dan Kemahiran Hukum dalam Menghadapi Dunia Kerja - Octora, Rahel (Zenit, 2014)
Work, often understood as something formal by students, is related with office work in a corporation or in an institution. The true meaning of work can be defined more widely. Work is an activity to get financial benefits, a means of self actualization as well as the application of knowledge. The meaning of work is included in being an officer, a professional, or an enterpreneur. This paper will specifically talk about legal education and the correlation between legal science and some kinds of jobs andoccupations. Fresh graduates have to be ready to face the fact that there are a lot of complaints from industries that graduates with Bachelor’s degree are not ready to work. After graduating from universities, they still need to join some training programs to improve their skills. Every faculty must design its curricula based on the need and demand of the workplace. It’s true that theory is important but practical skills are also important. In other words, hard skills are not enough. Proper curriculacan support student readiness to face the real work.Keywords: work, occupation, legal education, theory, skill.